EFFECTS OF DATE SUPPLIMENTATION AND CROSSING WITH DHOFARI GOATS ON THE FATTENING PERFORMANCE OF LOCAL GOATS IN THE UNITED ARAB EMIRATES - Alhadrami, G.A. (Emirates Journal of Food and Agriculture, 1996)
Please see the scanned pdf version in full text